2021
DOI: 10.3390/antibiotics10101157
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, Antimicrobial Resistance and Biofilm Production of Escherichia coli Isolates from Healthy Broiler Chickens in Western Algeria

Abstract: The aim of this study was to assess the virulence, antimicrobial resistance and biofilm production of Escherichia coli strains isolated from healthy broiler chickens in Western Algeria. E. coli strains (n = 18) were identified by matrix-assisted laser desorption–ionization time-of-flight mass spectrometry. Susceptibility to 10 antibiotics was determined by standard methods. Virulence and extended-spectrum β-lactamase (ESBL) genes were detected by PCR. The biofilm production was evaluated by microplate assay. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…These results, showing the multi-resistance of the majority of the isolates, confirm previous studies that reported a high level of multidrug resistant Enterobacteriaceae isolates from poultry in Algeria [ 23 , 32 ]. The causes of this antibiotic resistance phenomenon are very different, and the important cause is the massive and inappropriate use of antibiotics.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results, showing the multi-resistance of the majority of the isolates, confirm previous studies that reported a high level of multidrug resistant Enterobacteriaceae isolates from poultry in Algeria [ 23 , 32 ]. The causes of this antibiotic resistance phenomenon are very different, and the important cause is the massive and inappropriate use of antibiotics.…”
Section: Resultssupporting
confidence: 91%
“…Bacterial Strains Five Enterobacteriaceae isolates, four Escherichia coli, and one Klebsiella pneumonia were selected to carry out the study. The strains were isolated from poultry in the Regional Veterinary Laboratory of Mostaganem, Algeria, and identified using matrix-assisted laser desorption-ionization time-of-flight mass spectrometry (MALDI-TOF-MS), as previously reported [23]. E. coli ATCC 25922 and Staphylococcus aureus ATCC 6538 (American Type Culture Collection, Rockville, MD, USA) were also tested.…”
Section: Polyphenols Profile In Smmentioning
confidence: 99%
“…Messai et al [5] and Ibrahim et al [3] found high resistance to SXT at 82% and 95.50%, respectively. Resistance to CN, C, and NIT was higher than in Benameur et al [27], Halfaoui et al [19], Boutaiba Benklaouz et al [12], and Kazibwe et al [24]. The administration of these antibiotics is forbidden in veterinary medicine in Algeria.…”
Section: Discussionmentioning
confidence: 84%
“…Resistance to CN, C, and NIT was higher than in Benameur et al . [ 27 ], Halfaoui et al . [ 19 ], Boutaiba Benklaouz et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the European level, the effective implementation of different alternative measures in pig production, such as improvement of biosecurity, vaccination, improved feeding, and health care, has resulted in a significant reduction in AMU [ 61 ]. Adequate hygiene measures must be employed to alleviate underlying reasons of reoccurrence of avian pathogenic E. coli on poultry farms such as biofilm formation [ 62 , 63 ]. However, the implementation of alternatives in a hurdle system must be feasible for farmers, as they often require financial investments.…”
Section: Discussionmentioning
confidence: 99%